Impact of Government Policy on Tuna Commodities in Malang District, East Java - Yeni Sari Wulandari; Suhartini Suhartini; Hery Toiba (HABITAT, 2020)
Tuna commodity turns out to be one of fishery commodities contributing to an export increase by value above the average of 18.57%. This is an opportunity for Indonesia to improve the country's economy by utilizing existing fishery resources. Thus, government policies are needed in order to support the export performance of fishery products. This research was conducted to determine the impact of government policies toward tuna fish commodities in Malang. The method used was the Policy Analysis Matrix (PAM) that aimed at knowing the impact of government policies on tuna commodities. In this study, the respondents were 30 tuna fishermen at TPI Pondokdadap. The results of analysis showed that there were subsidies, taxes, and trade restrictions in input factor. Nonetheless, in output factor, fishermen did not receive subsidies. The existence of a policy on input is very helpful for fishermen so as to reduce production costs, while in the output policy the community receives more benefits at low output prices. However, it can be seen from the DRC and PCR values that they are less than one. This means that the tuna fish commodity in Malang still has comparative and competitive advantages in competitiveness.